Tradisi Bahandipan sebagai Bentuk Komunikasi Budaya Kolektif Petani Sawah di Desa Gudang Hirang - Yakub Amin, Muhammad; Alif, Muhammad (P3M Politeknik Negeri Media Kreatif, 2026)
Bahandipan tradition is a form of mutual cooperation unique to the Banjar community, which is now gradually being eroded by modernization. More than just an agricultural practice, this tradition serves as a medium of collective cultural communication that strengthens solidarity among farmers in Gudang Hirang Village. This study aims to understand the role of the bahandipan tradition as a form of collective cultural communication, using a qualitative approach and phenomenological method through interviews, observation, and documentation involving farmer group leaders, local historians, and village farmers. Utilizing Symbolic Interaction Theory, the study analyzes how social meaning is constructed through interactions within the tradition. The findings reveal that bahandipan functions as both verbal and symbolic communication, reinforcing social networks, the values of mutual cooperation, and consensus-based decision-making without formal structure. Although it is increasingly affected by modern wage-based labor systems, bahandipan remains regarded as a meaningful cultural heritage worth preserving in the context of development rooted in local wisdom.